ENTREPRENEURSHIP-BASED CURRICULUM DEVELOPMENT STRATEGY IN MADRASAH ALIYAH IN FACING GLOBAL CHALLENGES - Mustaqim Mustaqim; Muhammad Husain (Universitas Islam Negeri (UIN) Sumatera Utara, 2025)
This study aims to formulate an adaptive entrepreneurship-based curriculum development strategy to provide a strategic roadmap for transforming Madrasah Aliyah into an innovation center in the face of global challenges and digital economic disruption. The method used is a descriptive qualitative approach with data collection techniques through triangulation, combining participant observation, in-depth interviews with key informants (Headmaster, Vice Head of Curriculum, teachers, and students), and documentation studies. The results show that the curriculum development strategy is carried out through the integration of Islamic